IMPROVING STUDENTS’ WRITING ESSAY SKILL THROUGH PROBLEM-BASED LEARNING APPROACH IN SECOND GRADE HIGH SCHOOL OF SMAN 5 MAKASAR - Andi Rahmatia Karim (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine the improving the skill of writing essays for students of SMAN 5 Makassar through problem-based learning approach. This kind of research was CAR (Classroom Action Research) using four stages, planning, action, observation, and reflection, which are implemented in two cycles, namely cycle I and cycle II. The instrument used in this research was test and observation. with a qualitative approach that is done by calculating the class average namely calculating the percentage of student completeness classically, students are declared passed if obtained a value of more than 80. The number of samples was 26 students, namely 12 boys and 14 girls in class XI IPA 1. The results of the research showed that the skills writing essays on students' texts after applying the problem-based learning approach through the actions of the first cycle, the average value is 68.79 or 39.50% in the less category. Action cycle II average value of 86.20 or 91.69% in the good category. Based on the research results, it can be concluded that the application of a problem-based learning approach can improve the quality of the process and learning outcomes of essay writing for class XI students of SMAN 5 Makassar. In accordance with the conclusions, the researcher suggests Indonesian teachers to used problem-based learning approach in learning to write essays, because the problem-based learning approach is proven to improve the quality of the process and learning outcomes.